Comparative Analysis of Formwork Systems: Cost Efficiency and Time Management in Construction Projects - Auliyah Shabirah Supriyono; I Nyoman Dita Pahang Putra; Bambang Trigunarsyah (Science and Technology Research Centre Universitas PGRI Semarang, 2025)
Formwork systems are essential for achieving efficiency and sustainability in multi-story construction. This study compares the cost and time efficiency of multiplex and aluminum formwork systems for constructing beams and slabs on the 6th to 13th floors. Field observations and a literature review were employed to gather data using a mixed-methods approach. This study adopts a mixed-methods approach, combining quantitative and qualitative methods. The findings reveal that aluminum formwork requires 60 days to complete, compared to 112 days for multiplex formwork, saving 52 days. Regarding cost, aluminum formwork amounts to IDR 1,805,910,198, offering savings of IDR 159,540,423 compared to multiplex formwork at IDR 1,965,450,621. Graphical analysis highlights the advantages of aluminum formwork in optimizing project workflows and reducing delays. These results demonstrate aluminum formwork potential to enhance efficiency, minimize material waste, and support sustainable construction practices. Future research is encouraged to explore alternative materials and labor strategies to further advance sustainability in the construction industry.